2011
DOI: 10.1007/s00210-011-0706-y
|View full text |Cite
|
Sign up to set email alerts
|

Local renin–angiotensin systems in the genitourinary tract

Abstract: Local renin-angiotensin systems are common throughout the human body. Recent evidence supports the existence of such local renin-angiotensin systems in the penis, clitoris, bladder, ureter, internal anal sphincter, and urethral sphincter. Beyond its role in regulating blood pressure through its effects on vascular tone, sodium balance, and fluid homeostasis, angiotensin II serves a key role in affecting physiologic and pathophysiologic activities of the genitourinary tract. Just as angiotensin-converting enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 169 publications
(201 reference statements)
0
7
0
Order By: Relevance
“…In this regard, we are still trying to understand why some muscarinic antagonists exhibit a certain degree of bladder selectivity (Yamazaki et al 2011), and it is largely unknown whether a similar phenomenon exists for β 3 -adrenoceptor agonists. Moreover, it is well established that the function of the systemic renin-angiotensin system is in part regulated by β-adrenoceptors, in humans β 1 -adrenoceptors, but a local renin-angiotensin system also exists in the urogenital tract (Comiter 2012). β-Adrenoceptors are also known to affect the function of gap junctions in the heart (Salameh and Dhein 2011), and gap junctions also play a role in the regulation of bladder function (Roosen et al 2009).…”
Section: Perspectivementioning
confidence: 99%
“…In this regard, we are still trying to understand why some muscarinic antagonists exhibit a certain degree of bladder selectivity (Yamazaki et al 2011), and it is largely unknown whether a similar phenomenon exists for β 3 -adrenoceptor agonists. Moreover, it is well established that the function of the systemic renin-angiotensin system is in part regulated by β-adrenoceptors, in humans β 1 -adrenoceptors, but a local renin-angiotensin system also exists in the urogenital tract (Comiter 2012). β-Adrenoceptors are also known to affect the function of gap junctions in the heart (Salameh and Dhein 2011), and gap junctions also play a role in the regulation of bladder function (Roosen et al 2009).…”
Section: Perspectivementioning
confidence: 99%
“…Additionally, 20-30% of the systemic ANG production is believed to come from alternative pathways involving cathepsin G, chymase, and other serine proteases (Tsukamoto and Kitakaze, 2013). However, meanwhile it has become clear that renin, angiotensinogen, and ACE are not only formed in kidney, liver, and lung, respectively, but can also be expressed in many other tissues including heart (Tamura et al, 1997b), vessel wall, kidney (Siragy and Carey, 2010), adipose tissue (Cassis et al, 2008), gastrointestinal tract (Wong et al, 2007), or urogenital tract (Comiter, 2012), yielding a tissue renin-angiotensin system (RAS). Of note, there is also a tissue RAS in the brain, which mediates important physiologic functions, e.g., in the regulation of thirst or cognition Pelisch et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Local renin angiotensin system (RAS) is common in the human body and has been identified in the genitourinary tract, specifically in the bladder . Bladder muscle strips from human, canine, and rabbit have confirmed that angiotensin II (Ang II) is involved in bladder contraction and smooth muscle tone.…”
Section: Introductionmentioning
confidence: 99%